Paperbacks from hell : the twisted history of '70s and '80s horror fiction - Hendrix, Grady; Errickson, Will, 1970- (Philadelphia, PA : Quirk Books, 2017)
A nostalgic and unflinchingly funny celebration of the horror fiction boom of the 1970's and 1980's, complete with story summaries and artist and author profiles.
Hail, Satan -- Creepy kids -- When animals attack -- Real estate nightmares -- Weird science -- Gothic and romantic -- Inhumanoids -- Splatterpunks, serial killers, and super creeps -- Appendix : Selected creator and publisher biographies -- Afterword : Recommeded reading / Will Errickson.
Includes index.
Keywords: Horror tales -- History and criticism; Ghost stories -- History and criticism; Paperbacks -- History and criticism; Book cover art